The Deconstruction of the Femininity of the Main Character in Andrea Hirata's Ayah Novel: Throwing the Shackles of Community Conventions - Arini Vika Sari (Universitas Ahmad Dahlan, 2021)
This study aims to uncover the femininity contained in the novel Ayah by Andrea Hirata with the female main character Marlena and the male main character Sabari. This research is a qualitative descriptive research using critical discourse analysis method. The data source is the novel Ayah by Andrea Hirata published in Bentang 2017. The technique of collecting data is by reading and recording on a data card. The data collection instrument is the human instrument or the researcher himself using a postmodern feminism approach. In analyzing the data, it was carried out in three stages, namely (1) word reduction; (2) data presentation; and (3) drawing conclusions. The results of deconstruction of femininity show that there are six forms of deconstruction of femininity in Andrea Hirata's novel Ayah, namely: feminine image, feminine desire, beauty, feminine habits, feminine work, and feminine principles. Femininity in the novel Ayah is owned and practiced by the female main character and the male main character who have strengths and weaknesses. Through the deconstruction of postmodern femininity, Andrea Hirata is able to present the main character as the subject of the construction of femininity who tries to free himself from the shackles of society's conventions.